2006
DOI: 10.1111/rp10.1016-j.femsim.2004.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination preventsHelicobacter pylori-induced alterations of the gastric flora in mice

Abstract: Molecular analysis of the gastric microflora in mice revealed that Helicobacter pylori infection causes an increase in microbial diversity. The stomachs of H. pylori-infected animals were colonized by bacteria which are naturally restricted to the lower intestinal tract. Clostridia, Bacteroides/Prevotella spp., Eubacterium spp., Ruminococcus spp., streptococci and Escherichia coli were detected exclusively in the stomachs of infected animals, whereas lactobacilli dominated the gastric flora in noninfected mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 27 publications
3
47
1
3
Order By: Relevance
“…In fact, some of the included studies did not find significant differences using cloning (14) and culture-based approaches (19,21), whereas other studies report significant changes in gastric microbiota according to H. pylori status based on DNA microarrays (17) or 454-pyrosequencing (16), which allow the study of a wider range of bacteria, thus providing a more complete view of the picture. Animal studies have also yielded contradicting findings, as H. pylori infection altered significantly the constitution of gastric microbiota in a BALB/c mice model (27) and in Mongolian gerbils (28), but it does not significantly alter the murine gastric microbiota (29).…”
Section: Discussionmentioning
confidence: 89%
“…In fact, some of the included studies did not find significant differences using cloning (14) and culture-based approaches (19,21), whereas other studies report significant changes in gastric microbiota according to H. pylori status based on DNA microarrays (17) or 454-pyrosequencing (16), which allow the study of a wider range of bacteria, thus providing a more complete view of the picture. Animal studies have also yielded contradicting findings, as H. pylori infection altered significantly the constitution of gastric microbiota in a BALB/c mice model (27) and in Mongolian gerbils (28), but it does not significantly alter the murine gastric microbiota (29).…”
Section: Discussionmentioning
confidence: 89%
“…This potential colonization by bacteria in the stomach may help drive the continuing chronic inflammation seen in both our mouse model and in the human disease. One recent study has shown that the gastric microbiota of BALB/c mice infected with H. pylori does change from being predominately lactobacilli to including Clostridia, Bacteroides/Prevotella spp., Eubacterium spp., Ruminococcus spp., Streptococci, and E. coli (Aebischer et al 2006). The importance of this increased microbiological diversity on the progression to gastric adenocarcinoma has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the different stomach physiology of the gerbil (28,29) and the previously demonstrated crucial role of core chemotaxis factors for gerbil colonization (7), we reasoned that it might be very relevant to investigate the functions of H. pylori TlpD also in the gerbil. In particular, the pH in the gerbil stomach lumen is considerably lower than that in the mouse stomach lumen (30), close to the pH of 1 to 2 that is reached in the human stomach lumen, so bacterial abilities related to pH changes in the gastric mucosa might lead to a more severely attenuated colonization phenotype in the gerbil than in the mouse (28,29).…”
mentioning
confidence: 99%